Purified Smc5/6 Complex Exhibits DNA Substrate Recognition and Compaction - Gutierrez-Escribano, Pilar; Hormeño, Silvia; Madariaga-Marcos, Julene; Solé-Soler, Roger; O'Reilly, Francis J; Morris, Kyle; Aicart-Ramos, Clara; Aramayo, Ricardo; Montoya, Alex; Kramer, Holger; Rappsilber, Juri; Torres-Rosell, Jordi; et al. (Molecular cell, 2020)
Eukaryotic SMC complexes, cohesin, condensin, and Smc5/6, use ATP hydrolysis to power a plethora of functions requiring organization and restructuring of eukaryotic chromosomes in interphase and during mitosis. The Smc5/6 mechanism of action and its activity on DNA are largely unknown. Here we purified the budding yeast Smc5/6 holocomplex and characterized its core biochemical and biophysical activities. Purified Smc5/6 exhibits DNA-dependent ATP hydrolysis and SUMO E3 ligase activity. We show that Smc5/6 binds DNA topologically with affinity for supercoiled and catenated DNA templates. Employing single-molecule assays to analyze the functional and dynamic characteristics of Smc5/6 bound to DNA, we show that Smc5/6 locks DNA plectonemes and can compact DNA in an ATP-dependent manner. These results demonstrate that the Smc5/6 complex recognizes DNA tertiary structures involving juxtaposed helices and might modulate DNA topology by plectoneme stabilization and local compaction.